E- HEALTH MONITORING SYSTEM FOR REMOTE PATIENTS - G., Giri Sai Venkat Niranjan; Y., Bhaskarrao (International Journal of Psychosocial Rehabilitation, 2020)
This paper discusses, with great success, the creation of a wireless heartbeat and a microcontroller-based temperature monitoring device at reasonable expense. Technological advances in the area of medicinal research have been influential in the treatment and detection of diseases. One such development is a device for tracking heart rhythm. Heart rate is a significant safety feature related to the cardiovascular function of humans. The amount of heartbeat per minute is called heart rate, representing specific physiological factors such as hormone pressure, occupational stress and job engagement, somnolence, and autonomic nervous system control. Most individuals are still risking their lives due to heart disease and neglect of health treatment at the right time. Hence, in this project we are implementing an e-health monitoring system for remote patients.